2018
DOI: 10.1063/1.5032157
|View full text |Cite
|
Sign up to set email alerts
|

Transmodal elastic metasurface for broad angle total mode conversion

Abstract: It has been long believed that a total mode conversion between longitudinal and shear elastic waves can only be achieved at a certain incidence angle. Here, we show that a total mode conversion can be achieved for a broad range of incidence angles by a specially designed elastic metasurface, namely, transmodal metasurface. From the generalized reflection law, we found that the incident longitudinal wave can be totally converted to a reflected shear wave over a broad range of incidence angles if a sufficiently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 29 publications
0
34
0
1
Order By: Relevance
“…From the nephograms of the phase shift for the transmitted P-and SV-waves, as shown in Figs. 3(a) and 4(a), it can be found that the phase shift indeed has a full 2π coverage in a wide frequency range (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)). The corresponding wavelengths for the P-and SV-waves are 191 -127 mm and 111 -74 mm, respectively.…”
Section: The Metasurface and Tunable Functional Unitsmentioning
confidence: 93%
See 1 more Smart Citation
“…From the nephograms of the phase shift for the transmitted P-and SV-waves, as shown in Figs. 3(a) and 4(a), it can be found that the phase shift indeed has a full 2π coverage in a wide frequency range (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)). The corresponding wavelengths for the P-and SV-waves are 191 -127 mm and 111 -74 mm, respectively.…”
Section: The Metasurface and Tunable Functional Unitsmentioning
confidence: 93%
“…Furthermore, some works have reported on manipulating in-plane P-and SV-waves simultaneously, e.g. splitting of P-wave and SV-wave [35,36], converting P-wave to SV-wave [37] and manipulating multimodal ultrasonic guided waves [38]. Recently, topology optimization has been used to manipulate longitudinal and shear waves [39].…”
Section: Introductionmentioning
confidence: 99%
“…揭示了 单胞间有利耦合和不利耦合的内部机理, 并指出由于 聚焦型超构表面连续的相位变化使得所有相邻单胞间 图 8 (网络版彩图) (a) 无序弹性波超构表面 [115] ; (b) 非局部弹性波超构表面 转换只能在一定的入射角下产生. Kim等人 [83] 通过在 板结构边界设计平均长度约为P波波长一半的梯度波 导谐振子, 构成亚波长反射型超构表面, 实现了板结构 中入射P波在19°~90°的大入射角范围内, 全部模式转 换为剪切SV波, 为结构健康监测信号处理技术提供了 新的思路. 本文作者 [84] 也成功地将亚波长的弹性波超 (1) 随着研究工作的深入, 研究人员发现广义斯涅 尔定律对解释一些涉及高阶衍射的新现象不再有效, 如入射角超过所谓的临界角 [135,136] 和一些不被期望的 泄漏波 [48,74] .…”
Section: 可调板波超构表面unclassified
“…In light of that, the elastic metasurface has been recently developed to offer a preferable possibility to manipulate elastic waves (Zhu and Semperlotti, 2016;Kim et al, 2018;Su et al, 2018). Compared with metamaterials, metasurfaces are compact in size, easier to fabricate and with smaller losses (Liu et al, 2017;Li et al, 2018), because they only consist of single-or few-layer unit cells, to shape discontinuous physical fields between different regions (Chen et al, 2016;Assouar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%